2015
DOI: 10.3389/fnhum.2015.00045
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a Self-Alert Training (SAT) program in adults with ADHD

Abstract: Attention-Deficit/Hyperactivity Disorder (ADHD), a neuropsychiatric condition characterized by attention and impulsivity problems, is one of the most common behavioral disorders. The first line of treatment for ADHD is psychostimulant medication, but this has limited effectiveness, particularly in adults, and is often associated with adverse side-effects. Thus, it is imperative that new non-pharmaceutical approaches to treatment are developed. This study aims to evaluate the impact of a non-pharmacological Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
(78 reference statements)
0
21
0
3
Order By: Relevance
“…A number of studies have evaluated the efficacy of such interventions in the long-term, and demonstrated that it is maintained from 3 to 12 months after the end of the treatment (Safren et al, 2010 ; Salakari et al, 2010 ; Emilsson et al, 2011 ; Pettersson et al, 2014 ; Fleming et al, 2015 ; Salomone et al, 2015 ; Young et al, 2015 ; Cherkasova et al, 2016 ; Gu et al, 2017 ; Nasri et al, 2017 ), although the magnitudes of the reported effects are heterogeneous. The largest clinical trial so far published in the field found that groups receiving psychosocial therapy had superior outcomes to active control groups at follow-up only in the CGI measure, but not in ADHD symptoms (Philipsen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have evaluated the efficacy of such interventions in the long-term, and demonstrated that it is maintained from 3 to 12 months after the end of the treatment (Safren et al, 2010 ; Salakari et al, 2010 ; Emilsson et al, 2011 ; Pettersson et al, 2014 ; Fleming et al, 2015 ; Salomone et al, 2015 ; Young et al, 2015 ; Cherkasova et al, 2016 ; Gu et al, 2017 ; Nasri et al, 2017 ), although the magnitudes of the reported effects are heterogeneous. The largest clinical trial so far published in the field found that groups receiving psychosocial therapy had superior outcomes to active control groups at follow-up only in the CGI measure, but not in ADHD symptoms (Philipsen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação aos resultados obtidos pelas intervenções, destaca-se que, de maneira geral, todas apresentaram resultados positivos para redução dos sintomas do TDAH, bem como a redução de comorbidades como ansiedade, depressão e comportamento desafiador. De fato, a literatura apresenta diversos estudos que evidenciam os benefícios da TCC para indivíduos com TDAH, contribuindo tanto para a melhora dos sintomas do transtorno, como também para suas comorbidades (Salomone et al, 2015;Young et al, 2015). Conforme exposto, as principais dificuldades na implementação dessas intervenções referem-se a características comuns à fase da adolescência, tais como o receio de não ser aceito socialmente devido ao transtorno, a busca por maior autonomia para tomar decisões e um possível constrangimento com a participação dos pais.…”
Section: Resultsunclassified
“…Working memory problems and impaired sustained attention are characteristic symptoms of ADHD [2,57]. Improvement of symptomatology by cognitive training and psychological interventions aimed to increase the correlation between sustained attention and arousal has been evalued several times in the recent past [58][59][60][61]. However, benefits for behavioral transfer effects to measures of fluid intelligence after several weeks of a computerized working memory treatment requiring high cognitive load could not be confirmed satisfactorily and raised questions about the controversial usefulness of such training [22,24,62].…”
Section: Discussionmentioning
confidence: 99%